Wireless Video Monitoring of the Megacities Transport Infrastructure - Dmitry Kalistratov (Civil Engineering Journal, 2019)
The article discusses the development of megacities transport infrastructure. The problem of traffic congestion is touched upon, the task of optimal road design is justified. In the context of these issues gives a system of wireless video monitoring of traffic flows on base of digital panoramic video images. The main objective is to obtain a universal mathematical model for the description of a radio signal with any type of digital modulation. This will greatly facilitate the parametric calculation of the radio channel for image transmission and the design of the monitoring system. The objective is achieved by applying the Fourier method of separation of variables in combination with computer simulation methods. As result, a highly accurate universal mathematical model of radio signal with digital modulation is proposed. The scientific novelty of the model is that it allows to simulate the propagation of a radio signal with an arbitrary waveform. Thanks to this, the model covers almost all common types of digital modulation of the radio signal. In addition, the model takes into account the internal noise of the equipment and the external interference of the radio channel. The article describes in detail the process of solving the wave equation, underlying the model. Examples of modeling are given, the advantages and disadvantages of the model are indicated. Recommendations are made on its use for calculating radio channels and designing systems for analyzing and developing the transport infrastructure of a megacity.